Implementasi Program Kelompok Usaha Bersama Dalam Meningkatkan Kesejahteraan Masyarakat Miskin Di Desa Lancang Kuning Kabupaten Bintan - Lia Agustina; Jamhur Poti; Rudi Subiyakto (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
The Joint Business Group Program (KUBE) is a government program that aims to improve the welfare of the poor. The Joint Business Group (KUBE) was also established in one of the villages in Bintan Regency, namely Lancang Kuning village. However, several problems were also found in the implementation of the Joint Business Group (KUBE) program in the village: There were several obstacles in running the program, There was no specific strategy for marketing activity products, Problems with business capital that should be used for the development of Joint Business Groups. The purpose of this study was to find out the process of implementing the Joint Business Group (KUBE) program in Lancang Kuning Village in improving the welfare of the poor. This study uses the Edward III Model of policy implementation, communication, resources, dispositions, and bureaucratic structures. Interviews, observations, and documentation studies are data collection methods. The results of the study show that 1) communication indicators cannot be said to be optimal due to several factors, namely the government's inconsistency in providing socialization to the KUBE group. 2) The resource indicators in the process of implementing the KUBE program in Lancang Kuning Village have been declared successful, the indicators for human resources have been adequate from members and KUBE assistants. And from a financial point of view, it has also been good because the KUBE group has received a grant of 20 million at the beginning of the formation of KUBE. 3) disposition indicators can be seen that the government has paid attention to KUBE in Lancang Kuning Village, especially to KUBE who are active in KUBE program activities. 4) indicators of bureaucratic structure cannot be said to be optimal, because KUBE members do not understand how standard operational procedures (SOP) are in implementing the KUBE program. The conclusion is that the implementation of KUBE in Lancang Village has not run optimally, because community members do not understand the KUBE program.